Non-enzymatic glucose oxidation at electrocatalytic metal oxide films - LYONS, MICHAEL (Electrochemical Society, 2013)
The electro-oxidation of glucose at nickel hydroxide films is discussed. These films can be electrodeposited using a simple potential multi-cycling procedure. The resulting films exhibit a nanostructured surface morphology. Cyclic voltammetry, rotating- disk electrode voltammetry and electrochemical impedance spectroscopy have been used to elucidate the kinetics and mechanism of the oxidation of glucose. NiOOH is shown to be the active form of the nickel hydroxide layer and the impedance data indicates significant surface adsorption at these sites. Furthermore, mass-transport-corrected Tafel slopes of ca. 40 and 60 mV/dec were observed at low and high potentials respectively identifying a change in rate-control with increasing potential. Finally, we show using amperometric techniques that this simple modified electrode possesses excellent sensitivity for the oxidation of glucose, displaying current increases of ca. 3.7 mA mM?1 cm?2 with a limit of detection of the order of 2.0 ?M glucose.
ECS Transactions
223rd ECS Meeting
PUBLISHED
Toronto ON Canada
Keywords: Glucose oxidation; non-enzymatic glucose sensing; Nanoscience & Materials; Next Generation Medical Devices